Cities of youth: Post-millennial cases of mobility and sociality - Karen Tranberg Hansen (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2014)
With a focus on cities in eastern and southern Africa, this paper draws on recent scholarship and my own research in Lusaka, Zambia, to analyse pathways for, and challenges to, greater social mobility for youth against the background of economic, political, and spatial processes that are affecting urban livelihoods in the region, facilitating or hindering youth social mobility. The paper describes several forms of sociality that brings young women and men together around music, religion, and recreation, including sex. The solidarities and networks that result from such interactions help young people situate themselves in relation to others at the present and in relationship to the future, shaping the urban dynamic in the process.
Keywords: O15; O17; O55; 330; youth; urban space; social mobility; sociality; sexual relations